New developing narrow band IoT technology NB-IoT - Zhi-bin ZHENG; De CHEN; Hao WU (物联网学报)
The newly developing low power wide area(LPWA) cellular data access requirements and challenges of Internet of Things is introduced,then the design principle and standardization progress of NB-IoT technologies are analyzed.At last,several typical NB-IoT applications are described.NB-IoT will be the most competent LWPA technology,since NB-IoT has five technical advantages:flexible deployment,wide coverage,low power consumption,low cost and massive connections.